2021
DOI: 10.1122/8.0000260
|View full text |Cite
|
Sign up to set email alerts
|

Orientation effect on the rheology of graphene oxide dispersions in isotropic phase, ordered isotropic biphase, and discotic phase

Abstract: We present a combined simulation and experimental study of the structure and dynamics of dilute, semidilute, and concentrated graphene oxide aqueous alkaline dispersions. These materials behave as lyotropic systems, with phase ordering as the concentration increases. The sheet spacing in the ordered phases is much broader than that expected by the classical Derjaguin–Landau–Verwey–Overbeek theory. Rheological responses in the isotropic phase are similar to rod-like liquid crystals (LCs), which follow the simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…The shear-thinning behavior has previously been reported for flow-aligning nematic LCs and GO suspensions [38,47,48]. Choi et al [38] and Adnan et al [49] investigated the viscosity of GO suspensions for shear rates up to 10 s −1 and showed that it increased for different concentrations of GO from the isotropic to discotic phase.…”
Section: Concentrationmentioning
confidence: 75%
See 3 more Smart Citations
“…The shear-thinning behavior has previously been reported for flow-aligning nematic LCs and GO suspensions [38,47,48]. Choi et al [38] and Adnan et al [49] investigated the viscosity of GO suspensions for shear rates up to 10 s −1 and showed that it increased for different concentrations of GO from the isotropic to discotic phase.…”
Section: Concentrationmentioning
confidence: 75%
“…The shear-thinning behavior has previously been reported for flow-aligning nematic LCs and GO suspensions [38,47,48]. Choi et al [38] and Adnan et al [49] investigated the viscosity of GO suspensions for shear rates up to 10 s −1 and showed that it increased for different concentrations of GO from the isotropic to discotic phase. Giudice and Shen [48] explored GO aqueous suspensions viscosity further, considering the higher shear rate of 10 2 s −1 , and showed that the shear-thinning behavior becomes more noticeable at higher concentrations.…”
Section: Concentrationmentioning
confidence: 75%
See 2 more Smart Citations
“…In the former category, anisotropic materials suspended in the solvent are known to tend to develop preferential orientation under mechanical stimulus. For example, the rheological responses of graphene-based suspensions have been extensively studied; pronounced shear alignment phenomena are observed as the shear rate exceeds critical values. Because of the suspension’s fluidity, upon removal of the mechanical stimulus, this preferential orientation could decay, and the original order is therefore restored after resting/annealing; this transient process is associated with a characteristic relaxation time τ. If the solvent of the suspension is evaporated within a period of time t sufficiently shorter than the relaxation time (i.e., t ≪ τ), the preferential orientation is then preserved and built in permanently to the solid phase formed by the suspension after evaporation of the solvent, for example, freeze-dry. , τ is on the order of seconds/mins and more in graphene-based suspensions. , As such, one can synthesize macroscopic assemblies with preferred out-of-plane orientation.…”
Section: Scalable Approaches For Fabricating Textured Electrodesmentioning
confidence: 99%